Spectrophotometric Determination of Procaine Hydrochloride in pharmaceutical preparations Via Oxidative Coupling Reaction (Tikrit Journal of Pharmaceutical Sciences, 2023)
A simple, reliable and sensitive spectrophotometric method for the determination of trace amount of procaine hydrochloride in pure and in pharmaceutical preparations (injections) has been developed. The method is based on the oxidative coupling reaction of procaine hydrochloride with phenothiazine and in the presence of ferric nitrate to form a green-water-soluble dye, which is stable and has a maximum absorption at 610 nm. A graph of absorbance versus concentration shows that beer's law is obeyed over the concentration range of 50-2000 µg of procaine hydrochloride in a final volume of 25 ml or (2-80 µg.ml-1) with a molar absorpitivity of 5.51 x 103 L.mol-1.cm-1, a Sandell sensitivity of 4.28 x 10-2 µg.cm-2, a relative error was less than 1.98% and a relative standard deviation was better than 1.72% depending on the concentration. The optimum conditions for full color development are described and the proposed method was applied satisfactorily to pharmaceutical preparations containing procaine Hydrochloride using standard addition method.